P-719 Effect of frozen and thawed embryo transfer on metabolism of children in early childhood. (30th June 2022) - Wu, T; Dong, Z; Wu, Y; Huang, H
Abstract: Study question: We aimed to investigate the metabolic profile at age 1.5 – 4 years in chidren conceived from FET. Summary answer: Plasma concentration of ApoE, fasting insulin and 11 small molecule metabolities were different beween FET group and the NC group. What is known already: Rencently, we showed that FET-conceived male mouse offspring presented glucose metabolism dysfunction mainly manifesting insulin resistance. Observations from human studies indicate that body fat composition in IVF children is disturbed and children conceived by IVF/ICSI have a less favourable glucose and cardiovascular metabolic profile in childhood when compared with naturally conceived. But human study emphasised on metabolic profile of children concieved from FET is limited, one follow-up study have suggested that children conceived by FET often show abnormal lipid metabolism. Study design, size, duration: 284 children at early childhood (1.5-4 years) conceived from FET or naturally conceived were recruited based on the data from electronic Case Report Forms (e-CRF) in the International Peace Maternity and Child Health Hospital (IPMCHH) from September 2018 to November 2019. A total of 147 children (with 118 born after FET and 29 conceived naturally) was included for biochemical examination and metabolomics analysis. Participants/materials, setting, methods: The peripheral venous blood of 147 children aged 1.5 - 4 years (with 118 born after FET and 29 conceived naturally) was drawn in the fasting state (>8h). FBG was measured using a glucometer, plasma concentrations of TC, TG, HDL, LDL were measured by chemistry analyzer, commercial ELISA kits were used for the measurment of Apolipoprotein, insulin, leptin, CRP, FT3, FT4, and TSH. Metabolomic analysis was performed on an UPLC-MS/MS system against 210 metabolites. Main results and the role of chance: The results of present study revealed that the chidren conceived from FET have different metabolite profile than the naturally conceived children. Except for the higher BMI of chidren from FET group, ApoE and insulin were found respectivedly higher and lower in chidren from FET group than in NC group. As for metabolomic analysis, small metabolities which reflect intestinal fermentation such as second bile acid and short chain fatty acids was significantly higher in children conceived from FET; unsaturated fatty acids which are crucial for neurodevelopment was significanty lower in FET group. Limitations, reasons for caution: Firstly, due to the small sample size, larger sample size and a longer follow-up period will be needed to observe the long-term metabolic profile and neurobehavioral performance of offspring conceived from FET. Secondly, we did not rule out other factors that may have influence on the metabolism of children. Wider implications of the findings: To our knowledged, we demenstrated the metabolic profile of chidren born after FET in early childhood by metabolomic analysis for the first time.The fast insulin level was significant decreased in FET group than NC group, which is opposes to previous findings. Trial registration number: 2016YFC1000203